Goal oriented model for persuasive storytelling in improved game experience for elderly - Pan, Zhengxiang (Nanyang Technological University, 2021)
Serious games for health are beneficial in fostering a healthy aging population. However, health games are not as popular among elderly when compared to commercial games. From the inherent differences between health games and commercial games, and between elderly and the average player, the term “elderly health game experience” was identified and explained. This thesis delves into assessing aspects that are unique to the elderly health game experiences (EHGE), and subsequently, methods to enhance the EHGE. The efforts aim to promote adoption of health games among elderly which can help them age healthily down the road. In this thesis, a pre-study is first conducted to discover elements of the EHGE. Through phenomenological study of elderly players’ gameplay and sharing, health values, familiarity and human interactions are highlighted as important aspects of the EHGE. Health Game Experience Questionnaire (HGEQ) is subsequently designed to establish understanding of EHGE via creating an assessment tool. Constructs and question items are added into the pre-existing Game Experience Questionnaire, thereby extending its measurement capabilities into important aspects of the EHGE. The constructs are modelled and the HGEQ is validated as a whole through Confirmatory Factor Analysis and statistical tests in a subsequent quantitative study with 51 participants. The HGEQ is deemed to appropriately capture the additional aspects of the EHGE, and bears potential to serve as a good measurement tool to provide feedback of health game experiences among the elderly. The third part of this thesis presents our attempt to craft a positive health game experience for the elderly. The Goal-Oriented Storytelling Model (GSM) is proposed to provide a methodological, step-by-step approach to coach the elderly when they play a health game. The storytelling mechanism in GSM uses Propp’s theory to structure a gameplay session into discrete states, much like different points in a story. On the other hand, other GSM mechanisms (persuasion, goal setting and familiarity) suggest coaching techniques that can help the elderly overcome barriers and complete the game with good experience. Four coaching scenarios are proposed by referencing these different mechanisms. The coaching scenarios are modelled using the Goal Net, enabling it for future implementations using intelligent agents. A GSM implementation is proposed and applied to coach 20 elderlies who had little to no prior exposure to video games through a health game session. Through quantitative and phenomenological analysis of the gameplay process, GSM is demonstrated as an effective practice that improves elderlies’ game performance, game literacy and game experience. Phenomenological findings also highlight the essence of the coached game experiences as a “storified” learning journey complete with various character archetypes, made possible by coaching practices derived from GSM mechanisms. Through the combination of quantitative and qualitative methods, the HGEQ and GSM contribute towards the assessment and creation of positive health game experiences for the elderly, thus encouraging them to adopt health games and in extension, a healthy lifestyle. Finally, the contributions in this thesis can eventually help serious game designers or researchers alike find new ways to improve health games from new coaching perspectives.